Wannaqueue – an effective queue management application - Azahar, Aemir Fashaa’; Abdul Hamid, Abdullah Izzuddin; Johari, Ismail; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
The purpose of this paper is to help people to overcome the long queue problem by providing them an effective waitlist application through mobile and web based platform “WannaQueue”. “WannaQueue” is a business model which provides a waitlist platform for people to get their services without waiting too long through current queue management system. “WannaQueue” also provides the opportunity for business owners by providing them a platform to publish their business to the customers. Literature Reviews, benchmarking, Business Model Canvas (BMC), 4 Lenses of Innovation, and Value Proposition Design (VPD) have been used as the methodologies for this paper.